2014
DOI: 10.1002/2013jb010579
|View full text |Cite
|
Sign up to set email alerts
|

A transient method for measuring the DC streaming potential coefficient of porous and fractured rocks

Abstract: High-quality streaming potential coupling coefficient measurements have been carried out using a newly designed cell with both a steady state methodology and a new pressure transient approach. The pressure transient approach has shown itself to be particularly good at providing high-quality streaming potential coefficient measurements as each transient increase or decrease allows thousands of measurements to be made at different pressures to which a good linear regression can be fitted. Nevertheless, the trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 40 publications
3
59
0
Order By: Relevance
“…The experimental cell and measurement set-up is described in Walker et al (2014). The pore fluids were made up to approximately the correct salinity using distilled, deionized water that had been previously degassed.…”
Section: Apparatus and Methodologymentioning
confidence: 99%
See 3 more Smart Citations
“…The experimental cell and measurement set-up is described in Walker et al (2014). The pore fluids were made up to approximately the correct salinity using distilled, deionized water that had been previously degassed.…”
Section: Apparatus and Methodologymentioning
confidence: 99%
“…The streaming potential coefficient was then calculated from the gradient of the plot. This procedure was described in Walker et al (2014), where such a plot can be found as their Fig. 2.…”
Section: Apparatus and Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…Jaafar et al (2013) found the point of zero charge (pzc) of two types of core samples (sandstone and carbonate), where the voltage difference was measured at different pH of solution, but there were no further study on the effect of the degree of alkalinity to the streaming potential [9]. In 2014, Walker et al applied new pressure transient approach as a faster approach than the conventional measurement methods, where the measured streaming potential coupling coefficients and zeta potential were aligned with the findings by Vinogradov et al (2010) at high salinity [10,11]. Results obtained by Esmaeili et al (2016) agreed with the published experimental data, and much lower scattering in the data points was achieved for different saline injecting water [12].…”
Section: Introductionmentioning
confidence: 99%